Applying cultural anthropology : an introductory reader - Podolefsky, Aaron; Brown, Peter J.; Lacy, Scott M. (New York : McGraw-Hill Humanities/Social Sciences/Languages, 2013)
'The ninth edition of Applying Anthropology: An Introductory Reader is a collection of articles that provide compelling examples of applied research in cultural anthropology. In this age of globalization and increased cultural intolerance, the basic messages of public anthropology are more important than ever. This new edition offers ten new readings that refer to contemporary social issues such as religious belief, work and family, social class, food production, relationships, consumerism, the effects of climate change on culture, and globalization'--
Includes bibliographical references and index.
Keywords: Ethnology; Applied anthropology